Analisis dan Desain Sistem Informasi Inventory Berbasis Web Menggunakan Metode Waterfall (Studi Kasus: Gama Studio Coffeeshop Jayapura) - Azra Nayla Istiazah; Heru Sutejo; Anisa Dwi Lestari (Tamilis Synex: Multidimensional Collaboration, 2026)
Effective inventory management is an important factor in maintaining the smooth operation of a business, including Gama Studio Coffeeshop Jayapura Papua. Currently, the process of recording inventory at Gama Studio Coffeeshop is still done manually using notebooks, which has the potential to cause recording errors, delays in stock information, and the risk of data loss. This study aims to design a web-based inventory system that can help the inventory management process more effectively and efficiently. The system development method used is Waterfall, which consists of the stages of needs analysis, system design, implementation, testing, and maintenance. Data collection was carried out through observation, interviews, and literature studies. The system design uses Use Case Diagrams, Activity Diagrams, and Class Diagrams as the basis for system development. The results of the study show that the designed web-based inventory system can facilitate admins in managing item data, supplier data, incoming goods transactions, outgoing goods transactions, and stock reports more quickly and accurately. This system is expected to minimize manual recording errors, improve operational efficiency, and support better decision-making in inventory management.